FACTORS INFLUENCING RATE OF RETURN OF SECURITIES IN THE STOCK EXCHANGE OF THAILAND UNDER SET WELL-BEING INDEX (SETWB) - Mo-on, Thamonwan; Pongsupatt, Tharinee (Journal of Buddhist Education and Research (JBER), 2023)
the purpose of this study was to explore factors influencing rate of return of securities in the stock exchange of Thailand under SET Well-Being Index (SETWB). In this study used secondary data of companies under the SET Well-Being Index (SETWB). The sample of 26 companies, collected quarterly from the 1st quarter of 2019 to the 4th quarter of 2021. This study examined seven independent variables including share turnover (TURN), size of firm (SIZE), return on asset (ROA), exchange rate between baht and US dollars (EXRATE), net trading of foreign investors (FOREIGNTRADE), debt to equity ratio (DE) and consumer price index (CPI). Multiple Regression analysis was adopted for this study and this data was analyzed by qualitative and quantitative data analysis using the Panel Least Squares Method, Random Effect Regression Model (REM). The results showed that information factors influencing rate of return of securities in the stock exchange of Thailand under SET Well-Being Index (SETWB) with positively statistical significance level of 0.05 was share turnover (TURN), exchange rate between baht and US dollars (EXRATE) and net trading of foreign investors (FOREIGNTRADE). Meanwhile, consumer price index (CPI) had negative correlation to rate of return of securities in the stock exchange of Thailand under SET Well-Being Index (SETWB) with an R-Square of 0.3470.